The Suppressing Effects of Dkk3 Expression on Aggressiveness and Tumorigenesis of Colorectal Cancer - Zhao, Shuang; Hao, Chang-lai; Zhao, En-hong; Jiang, Hua-mao; Zheng, Hua-chuan (Frontiers in Oncology, 2020)
Dkk3 has been discovered during comparison of immortalized and parental cells. Its expression has been shown to reduce colony formation and induce apoptosis of cancer cells, acting as a tumour suppressor. Herein, we demonstrated that Dkk3 overexpression or protein treatment may inhibit colorectal cancer cell proliferation, migration, and invasion, and that they may promote apoptosis and G2 phase arrest with hypoexpression of Bcl-2, cdc25B, cdc25c, N-cadherin, slug and twist, and hyperexpression of Bax and E-cadherin. This effect is consistent with that of recombinant Dkk3 exposure and blocked with anti-Dkk3 antibody. Dkk3 deletion in intestinal cells was not associated with emergence of epithelial lesions; however, adenoma emerged after sodium desoxycholate treatment. At both mRNA and protein levels, Dkk3 expression was higher in normal than in cancer tissues (p<0.05). Dkk3 mRNA expression was negatively associated with its promoter methylation, growth pattern, differentiation and favorable prognosis in the patients with colorectal cancer (p<0.05). Dkk3-related signal pathways in colorectal cancer included those of cellular adhesion and migration, melanogenesis, chemokine, Hedgehog, JAK-STAT, TOLL-like receptor, TGF-β, MAPK, and calcium signaling (p<0.05). These findings indicate that Dkk3 expression levels can help assess cancer aggressiveness and patient prognosis. It might also suppress aggressive phenotypes and tumorigenesis as a molecular target in gene therapy.